Camel milk exosomes modulate cyclophosphamide-induced oxidative stress and immuno-toxicity in rats. Issue 11 (1st November 2019) - Ibrahim, Hany M.; Mohammed-Geba, Khaled; Tawfic, Amr A.; El-Magd, Mohammed A.
Abstract : Camel milk proteins exhibit many beneficial properties including immuno-modulatory and anti-oxidant effects. Abstract : Camel milk proteins exhibit many beneficial properties including immuno-modulatory and anti-oxidant effects. Recent studies demonstrated that most of these properties are ascribed to the presence of extracellular nanovesicles known as exosomes. Therefore, the current study aimed to investigate the effect of the immuno-modulatory and anti-oxidant properties of camel milk exosomes on the immuno-toxicity and oxidative stress induced by cyclophosphamide (CTX) in albino rats. Exosomes were isolated from camel milk and exosomal kappa casein and lactoferrin mRNAs were detected and then sequenced. CTX was used to induce immunosuppression in rats, which were further treated with camel milk and its exosomes. The alterations in biochemical parameters, antioxidant status, cytokine profile, spleen histopathology and flow cytometric analysis were detected. Treatment with CTX resulted in a significant decrease in total protein, albumin, globulin, catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) levels associated with a significant increase in the levels of malondialdehyde (MDA) when compared with the control group. Moreover, CTX depleted lymphocytes in the spleen tissue, significantly reduced the expression of interferon gamma (IFN-γ) in the spleen cells and decreased the CD4 + and CD8 + cell percentages in the blood and spleen, while it induced a significant increase in the expression of interleukin (IL)-6 and tumor necrosis factor (TNF)-α. Co-administration of camel milk exosomes was able to normalize the antioxidant status and most of the biochemical and immunological parameters. This study clarifies that camel milk and its exosomes successfully ameliorate immunosuppression and oxidative stress induced by CTX in rats.